Energy finance strategy and governance nexus with economic growth: Results from emerging economies. - Md Mominur Rahman; Fataraz Zahan; Md Farijul Islam (PLoS ONE)
The rapid economic development in emerging economies, particularly in BRICS nations, is closely intertwined with their energy consumption and financial investment in energy sectors. However, the global shift towards sustainability has raised concerns about the continued reliance on fossil fuels and the environmental implications of such practices. Energy finance-particularly the balance between fossil fuel energy finance (FFEF) and renewable energy finance (RENF)-plays a critical role in shaping economic growth trajectories in these economies. At the same time, governance frameworks can either enhance or hinder the effectiveness of energy finance strategies. As the global push for sustainability intensifies, the need to balance these two energy sources becomes increasingly important. This study investigates the impact of energy finance on economic growth in BRICS nations and explores how governance moderates these relationships. Using data from the World Development Indicators (2000-2023) and employing econometric models, including Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS) for robustness, the findings reveal that both FFEF and RENF positively impact EGR. However, RENF also offers the added benefit of environmental sustainability, positioning it as a viable alternative for economic development. Good governance emerges as a critical factor that can mitigate the negative environmental effects of FFEF and further amplify the positive impact of RENF on EGR. The study highlights that BRICS nations have the option to shift from FFEF to RENF, as RENF not only promotes economic growth but also aligns with environmental goals. Strengthening governance frameworks will be essential in facilitating this transition and supporting sustainable economic growth.